The effect of CIPPA instructional model and inquiry method on nursing students' achievement and scientific attitude - Suwanida Anjirawaroj (University of Muhammadiyah Malang, 2020)
A good comprehension in the both theoretical and practical principles aspects is crucial for nursing students to achieve scientific achievement and attitude. The purpose of this research was observing the effect of CIPPA instructional model on nursing students’ scientific achievement and attitude. The population of this study was 110 nursing students who were in first semester of the academic year 2018/2019. The samples were selected and divided equally into two groups by using cluster random sampling technique. The first group was taught by using inquiry method instructional model while the other was taught using CIPPA instructional model. The research instruments were three plans of inquiry method and CIPPA instructional model, Biology for Health Science Achievement and Students’ Scientific Attitude tests. The data analysis techniques used mean, standard deviation, and t-test. The study results showed that there was no significant difference between the two groups observed in both scientific achievement [t(53) = 0.42, p = .81] and attitude [t(53) = 1.12, p = .313]. Interestingly, albeit that students’ perseverance and responsibility reached the highest score yet their rationality placed in the lowest level. Hence, more intensive and detail attention need to be given in all aspects of students’ scientific attitude.